AN APPROACH TOWARDS BUILDING SKILL COMPETENCIES IN NORTH-EAST INDIA - Bansal , Kapil (International Journal of Psychosocial Rehabilitation, 2020)
This research paper is a study about the various resource management programmes in the different areas of North-East regions. Different skill development institutions have been developed for the upliftment of the areas. The enhancement of the skills becomes necessary in these areas to get the fruits of the available natural resources. Actually the resource in these areas is very high but the society is not having the competency, therefore in order to uplift these areas various programmes have been laid down by the government. Government of India has also given various types of funding to various agencies for upliftment of the areas by building the sufficient sills, The Rural people participation in the process of development, and this type of development fulfills the priorities of the community, and becomes the foundation for the sustainable development, evident and a good sign of self-development, fixing its own goals and gains control upon the utilization of its own resources. Therefore this paper identifies the need, implementation and outcome of the programme laid down by the government and its success.